Linguistic Variation in the Ancrene Wisse, Katherine Group and Wooing Group Essays Celebrating the Completion of the Parallel Text Edition - Tanabe, Harumi; Tanabe, Harumi (Peter Lang, 2018)
Among thirteenth-century English devotional writings, the (S0(BAncrene Wisse(S1(B, the Katherine Group and the Wooing Group are central to debate about a putative standardised English, the AB Language. This book consists of articles investigating the manuscripts, textual transmission, punctuation, spelling, grammar and vocabulary of the (S0(BAncrene Wisse(S1 (BGroup. All the contributors use data taken from the parallel manuscript editions published by the Tokyo Manuscript Reading Group. The articles exemplify ways of using such parallel-text editions for linguistic and literary analysis. They present new findings on lexical and morphological divergences, which taken together cast light on scribal variation in texts transmitted in manuscript.s